Věcné styly ve vzdělávání bohemistů-cizinců - Čechová, Marie (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2015)
In the higher stage of linguistic studies, including foreigners, should occupy a prominent place substantive issues of factual styles, because the factual communiqué forms a major part of the professional activity of scientists, translators, interpreters and teachers. The study presents the objectives, content, methods and forms of activity in this discipline based on the author’s experience with the teaching of foreigners, most recently at the Institute of Czech Studies at the Faculty of Arts.
Keywords: fact style; bohemist-foreigners; creation; reception; interpretation of factual texts